350 Calcium Monitoring After Thyroidectomy: A Multidisciplinary Approach to Effective Test Utilization. (11th January 2018) - Brown, Alexandra; Ray, Amrita; Jackson, Lana
Abstract: Introduction: Hypocalcemia is a known risk in patients undergoing total thyroidectomy due to injury or removal of parathyroids. There is considerable variation in calcium monitoring practice patterns among surgeons performing thyroidectomies, and varying recommendations in the otolaryngology literature. Often, surgeons order multiple calcium and parathyroid hormone (PTH) assays to aid in postoperative decision making. The purpose of our study was to combine the expertise of pathology and otolaryngology to establish a standardized practice for postoperative calcium monitoring that provided adequate information for patient management, while not initiating excessive testing. Methods: Laboratory test ordering practices were abstracted from our clinical improvement database. Cases were identified from billing data for cases coded total thyroidectomy from June 2012 to June 2016. For each operative encounter, the number of calcium and PTH tests were recorded, along with the lab values. Discharge summaries and follow-up notes were searched for signs and/or symptoms of hypocalcemia, and whether patients presented to the emergency department or were readmitted within 30 days of discharge secondary to hypocalcemia. These data were used to plan the testing protocol, which was established as obtaining one PTH assay within one hour of gland removal, and discharging all patients on a tapering dose of calcium, with the addition of vitamin D for patients with a PTH level less than 10 pg/mL. Patients were followed for signs and/or symptoms of hypocalcemia, emergency department visits. or readmissions within 30 days of discharge secondary to hypocalcemia. Compliance with the protocol was monitored. Conclusion: There was considerable variation in test ordering among our surgeons, without a significant difference in patient outcome. After initiating our standardized protocol, utilization dropped significantly, without an increase in symptomatic hypocalcemia. The surgeons found this protocol easy to follow, and no longer felt they had to wait for test results for discharge.